Transmodulation of Dopaminergic Signaling to Mitigate Hypodopminergia and Pharmaceutical Opioid-induced Hyperalgesia - Brewer, Raymond; Blum, Kenneth; Bowirrat, Abdalla; Modestino, Edward J.; Baron, David; Badgaiyan, Rajendra D.; Moran, Mark; Boyett, Brent; Gold, Mark S. (Current Psychopharmacology, 2020)
Neuroscientists and psychiatrists working in the areas of “pain and addiction” are asked in this perspective article to reconsider the current use of dopaminergic blockade (like chronic opioid agonist therapy), and instead to consider induction of dopamine homeostasis by putative pro-dopamine regulation. Pro-dopamine regulation could help pharmaceutical opioid analgesic agents to mitigate hypodopaminergia-induced hyperalgesia by inducing transmodulation of dopaminergic signaling. An optimistic view is that early predisposition to diagnosis based on genetic testing, (pharmacogenetic/pharmacogenomic monitoring), combined with appropriate urine drug screening, and treatment with pro-dopamine regulators, could conceivably reduce stress, craving, relapse, enhance well-being and attenuate unwanted hyperalgesia. These concepts require intensive investigation. However, based on the rationale provided herein, there is a good chance that combining opioid analgesics with genetically directed pro-dopamine-regulation using KB220 (supported by 43 clinical studies). This prodopamine regulator may become a front-line technology with the potential to overcome, in part, the current heightened rates of chronic opioid-induced hyperalgesia and concomitant Reward Deficiency Syndrome (RDS) behaviors. Current research does support the hypothesis that low or hypodopaminergic function in the brain may predispose individuals to low pain tolerance or hyperalgesia.
Keywords: opioid analgesics